Towards realistic parametrization of the kinetic anisotropy and the resulting instabilities in space plasmas. Electromagnetic electron–cyclotron instability in the solar wind. Issue 3 (2nd December 2014) - Lazar, M.; Poedts, S.; Schlickeiser, R.; Dumitrache, C.
Abstract: Measured in situ, the particle velocity distributions in the solar wind plasma reveal two distinct components: a Maxwellian (thermal) core, and a less dense but hotter suprathermal halo with a power-law distribution described by Lorentzian/Kappa distribution function. Despite this evidence, the existing attempts to parametrize anisotropic distributions and the resulting wave instabilities are limited to idealized models, which either ignore the suprathermal populations, or minimize the core, assuming it is cold. Here, a more realistic approach is identified, combining an isotropic Maxwellian core and an anisotropic bi-Kappa halo. This model is relevant at large heliocentric distances and for the slow winds, when the field-aligned strahl is less pronounced and kinetic energy densities in the core and halo are comparable. A comparative study with the cold-core-based model is performed on the electron whistler–cyclotron instability driven by the anisotropic halo. Derived exactly numerically, the instability thresholds and growth rates confirm the expectation that cyclotron instabilities are inhibited by the core thermal spread. This effect is enhanced by the increase of the halo–core relative density with heliocentric distance, suggesting that local conditions for this instability to develop at large radial distances in the solar wind are less favourable than predicted before.